Comparison between laparoscopically assisted and standard fetoscopic laser ablation in patients with anterior and posterior placentation in twin‐twin transfusion syndrome: a single center study. (1st March 2015) - Shamshirsaz, Alireza A.; Javadian, Pouya; Ruano, Rodrigo; Haeri, Sina; Sangi‐Haghpeykar, Haleh; Lee, Timothy C.; Molohon, Jayme; Cass, Darrell L.; Salmanian, Bahram; Mollett, Laura; Moaddab, Amirhossein; Espinosa, Jimmy; et al.
Abstract Background The objective of our study was to compare outcomes following laparoscopically assisted procedure (LAP group) with those seen following a standard approach used in patients with either an anterior placenta (SAP group) or posterior placenta (SPP group). Method This was a retrospective review of all the cases of twin‐twin transfusion syndrome treated in our fetal center from October 2011 to July 2013. Technical characteristics of the procedure, perinatal survival outcome, and maternal morbidity were compared. Results The laser procedure time was significantly longer in the SAP group (44 ± 10 min) in contrast with SPP (19.3 ± 13.9 min, p < 0.001) and LAP group (32 ± 11 min, p: 0.012). Preterm premature rupture of membranes (PPROM) before 32 and 34 weeks of pregnancy was significantly more common with LAP versus SAP and SPP (90 vs 33.3 and 70.8% for 32 weeks respectively, p: 0.015; 100 vs 50 and 79.1% for 34 weeks respectively, p: 0.021). In terms of maternal morbidity and neonatal outcome, there were no significant differences between the three groups. Conclusion LAP may be useful in cases where SAP is not feasible. Despite the increased risk of PPROM with LAP, perinatal survival and maternal outcomes are similar to that seen in SAP and SPP patients. © 2015 John Wiley & Sons, Ltd.